Answer:
Step-by-step explanation:
exponents raised to a - power is an inverse function probably not the right word
a^-b = 1/(a^b) example 4^-2 = 1/(4^2) = 1/16
so (7^-1)^-1 is a double inverse which is back to the original number 7
inverted 7 twice
(7^-1)^-1 = (1/7)^-1 = 1/(1/7) = 7 trust me or use your calculator
since the coeffients are the same just add the powers... some exponent rule
5^2 * 5^4 * 5^-3 = 5^(2+4-3) = 5³
here is it written out
5^2 * 5^4 * 5^-3 = 5² × 5^4 × 5^-3 = (5×5) × (5×5×5×5) × (1/5×1/5×1/5)
5×5 × 5× (5×5×5 × 1/5×1/5×1/5) (5×5×5 × 1/5×1/5×1/5) = 1
5×5×5 = 5³
so